Peran Pemerintah Desa dalam Meningkatkan Kualitas Pelayanan Publik - Khairani Alawiyah Matondang; Putri Kemala Dewi Lubis; Endang Endang; Fera Daniaty Nababan; Putri Titin Sianturi (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Service is the main task of state apparatus. The scope of public interest services and services covers a broad field of public life. This mandate is contained in the 4th paragraph of the Preamble of the 1945 Constitution, but in practice, Indonesian public services have not run well. Provisions of public service to public civil servants are actually the result of the functioning of state institutions as civil servants. Therefore, the position of government agencies in staffing is very strategic because it determines the extent to which the government can best serve the community. .According to the purpose of the establishment. The results of this study indicate that the role of the village government in improving the economy of rural communities can be seen from the indicators of this study: governance, development implementation, community empowerment, and village community empowerment. The research method used to compile this article is a library survey. That is, reviewing the journal references we find and adapting them to the topic of this article. Based on the literature and reviews conducted in these journals, we found an impact between the welfare of teaching staff and improving the quality of education.